#### Answer

x = -2
y = -1

#### Work Step by Step

2x - 5y = 1
3x + y = -7
to the second equation solve y = -7 - 3x becouse
3x + y - 3x = -7 - 3x minus 3x to both sides
y = -7 - 3x
Substitude y = -7 -3x to the first equation
2x - 5 ( -7 - 3x ) = 1
2x + 35 + 15x = 1 use the distributive property
17x + 35 = 1 simplify
17x + 35 - 35 = 1 - 35 minus 35 to both sides
17x = -34
$\frac{17x}{17}$ =$\frac{-34}{17}$ divide both sides by 17
x = -2
y = -7 - $3\times(-2)$ substitude x for -2 to y = -7 -3x
y = -7 + 6
y = -1